Sobre el derecho : modelos para una introducción elemental - Dolabjian, Diego Alberto (2013)
This paper proposes an analytical model for the thorough exploration of the various positions on the Law, aiming to serve to the study of the different conceptions -both classic and contemporary- of the Natural law, Legal positivism and Legal realism.